THE URGENCY OF FORENSIC ACCOUNTING EXPERTISE IN EFFORTS TO PROVE FRAUD AND CORRUPTION - Arthur Frengki Kaharu; Femilia Zahra; Muhammad Ikbal Abdullah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Efforts to eradicate corruption involve various steps including strict law enforcement, strengthening the integrity of state institutions, increasing public awareness, and improving the monitoring and transparency system. The term forensic accounting in Indonesia emerged after the success of Pricewaterhouse Coopers (PwC) in uncovering the Bank Bali case. The PwC office was able to show a complex flow of funds in the form of a diagram of light emerging from the sun (sunburst). This research is a normative research that studies the purpose of law, values ​​of justice, validity of legal rules, legal concepts, and legal norms. Forensic accounting is a very effective tool in uncovering financial fraud in public companies. Not only operating on financial data analysis, forensic accountants are also trained to understand and apply relevant legal principles. They are able to identify suspicious patterns and compile evidence that is acceptable in court. This skill becomes very important, especially when fraud involves complex schemes hidden in layers of seemingly legitimate transactions. The role of Forensic Accountants is vital in efforts to prevent and reduce corruption. The better the implementation of forensic audits, the more optimal fraud prevention can be carried out. With a proactive and solution-oriented role, forensic accountants have the potential to contribute to the prevention and reduction of corruption at various levels, from the corporate level to the national level.